(untitled) (World Science, 2020)
The article presents the results of the study of the structure of personal activity motivation in the process of finding a job, highlights the main components that influence motivation and allow you to identify the motives that motivate a person to find a job. Using the factor analysis method, it is shown that the motivation of jobseekers in different types of employment has a multidimensional structure, the five most important factors were identified and analyzed, an attempt was made to determine the system of relevant key factors, psychological components and the structure of their relationships, external and internal conditions that promote or interfere with motivational processes.